Leverage and Earnings Management: Firm Size Moderation in Indonesian Industrial Firms - Eni Srihastuti; Sulthon Afzani (LP2M IAIN Palopo, 2026)
Abstract Purpose: This study investigates the firm-level determinants of accrual-based earnings management among Indonesian industrial firms, focusing on leverage, firm size, and their interaction. It hypothesises that leverage positively affects the magnitude of discretionary accruals (H1), firm size negatively affects it (H2), and firm size moderates the relationship between leverage and earnings management (H3). Methods: Using purposive sampling, the sample comprises 41 industrial-sector firms listed on the Indonesia Stock Exchange over the 2023–2025 period, yielding 123 firm-year observations. Earnings management is proxied by the absolute value of discretionary accruals from the cross-sectional Modified Jones Model. Two nested ordinary least squares models, namely a baseline and a moderation specification, are estimated with year fixed effects and firm-clustered standard errors, with all continuous variables winsorised at the 1st and 99th percentiles. Results: firm size is negatively and marginally associated with discretionary accruals (p = .073), offering modest support for the political cost hypothesis, whereas leverage's main effect is positive but statistically weak. Sales growth emerges as the most robust positive determinant of accrual magnitude, and the interaction between leverage firm size is positive and marginally significant, indicating amplification rather than attenuation of the relationship for larger firms. Implications: Auditors should treat sales growth as a salient operational risk signal when designing substantive procedures, and regulators may use the evidence to support differentiated audit-risk frameworks. Future research should extend the analysis to multi-sector panels and incorporate real activities manipulation proxies.